Aplicación de conceptos de la Teoría Comunicacional Del Derecho (TCD) a la normatividad laboral colombiana (2016)
In the present paper it aims at letting it know the application of concepts of the Communicational Theory of Law, as a basis to study and policy analysis of all areas of law and is related to the syntactic and semantic importance of legal standards.A broad concept catalogue has been created with a legal analysis of Colombian work policy that is in the law of 789 of 2002 and other complementary rules. The carelessness of legislators and drafters with the application of semantics and syntax in the drafting of legal norms is often commited in this legalistic country by nature.